Impacts of COVID-19-induced national lockdown on agriculture and rural livelihoods in India: A macro perspective - Tripathi, Gaurav; Pathak, Himanshu; Kumar, Anjani (Indian Society of Agricultural Economics, 2021)
In the last year and a half, COVID-19 has disrupted economies and livelihoods across the world, as well as causing large-scale infections and deaths. In this paper, an attempt has been made to analyse the economic impacts of COVID-19-induced lockdowns in India, with an emphasis on the agricultural sector and rural economy. The study has found that although, production, growth, and trade were affected less adversely in the agricultural sector than in the other sectors; the lockdowns had huge bearing on unemployment, incomes, and consumption in both rural and urban areas. The findings also indicate that the people in the urban areas suffered more than those in the rural areas; and that people in the bottom quintile were more adversely affected than those in the top quintile. COVID-19 thus worsened the already slow economy, and post-lockdown, it is yet to fully recover.